Biomechanical Properties of Land Based and Shallow Water Wait: A Comparative Review of Literature A Comparative Review of Literature - Yaghoubi M; Fink P; Page WH; Shultz SP (ScholarWorks@BGSU, 2021)
Aquatic locomotion exercises are frequently used in rehabilitation and cross-training for land-based athletes. Hydrostatic pressure, thermal conductivity and drag force affect a person's ability to move; therefore, it is important to understand differences of biomechanical gait in water vs land. This review investigated biomechanical differences between shallow water and land-based exercises. PubMed, Google Scholar, SPORTDiscus and Scopus were searched; 33 studies included walking forward (27), backward (6) and running (6). Electromyographic amplitude was similar or less in submaximal intensity during aquatic gait, in comparison to on land. At maximal intensities, however, the amplitude was similar (n=5) or higher (n=4) in water than on land. Kinetic variables (i.e. ground reaction force, lower extremity joint moments) were reduced in water (about 30-35%), while kinematic variables varied between shallow water and land-based exercise. The research highlighted in this review provides a strong foundation for improving rehabilitation and research practices associated with aquatic activities
This Scientific Literature Review is brought to you for free and open access by the Journals at ScholarWorks@BGSU. It has been accepted for inclusion in International Journal of Aquatic Research and Education by an authorized editor of ScholarWorks@BGSU.
Keywords: aquatic exercise; kinematics; kinetics; electromyography